Fracture risk and survival outcomes of radium-223 therapy for bone metastases in mCRPC and the modulatory role of bone-protective therapy: a systematic review and meta-analysis - Xiao, Mingzhong; Liu, Fan; Duan, Hong (Frontiers in Oncology, 2026)
BackgroundMetastatic castration-resistant prostate cancer (mCRPC) frequently involves the skeleton. While Radium-223 (Ra-223) alleviates symptomatic bone lesions, its effect on overall survival (OS) and fracture risk is debated. Bone-protective agents (BPAs) may play a critical modulatory role. This study systematically examined how Ra-223 influences OS and fracture risk and the effect of concomitant BPA use.MethodsAs per Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, PubMed, Embase, the Cochrane Library, and Web of Science were retrieved for randomized controlled trials (RCTs) and cohort studies through July 14, 2025. The primary outcomes were OS and fracture incidence in this PROSPERO-registered review (Registration No.: CRD420251102769). Hazard ratios (HRs) with 95% confidence intervals (CIs) were preferentially extracted; relative risks (RRs) were used when necessary. Heterogeneity was assessed using the I² statistic to guide the choice of random-effects versus random-effects models. Leave-one-out sensitivity analyses were conducted, and study quality was appraised using the NIH tool for RCTs and the Newcastle-Ottawa Scale (NOS) for cohort studies.ResultsNine studies were included, including six RCTs and three cohort studies. The pooled OS analysis (five studies, n=3,671) showed no significant benefit (HR = 0.82, 95% CI: 0.60-1.11; I²=79.8%). Excluding one study on an abiraterone background revealed a survival advantage (HR = 0.71, 95% CI: 0.61-0.81; I²=43.5%). For fracture risk, pooled analysis (five studies, n=3,671) showed no significant increase (HR = 1.32, 95% CI: 0.68-2.58; I²=89.1%). Concomitant BPA use (3 studies, n=279) was associated with a substantial fracture risk reduction (RR = 0.23, 95% CI: 0.11-0.45; I²=0.0%).ConclusionsCurrent evidence suggests that Ra-223 administered alongside standard therapy is not associated with statistically significant differences in OS or fracture risk among patients with mCRPC. Concomitant BPA therapy significantly reduces fracture incidence. Therapeutic context, including concurrent therapies and sequencing, may influence survival. Routine evaluation and consideration of BPA use during Ra-223-based regimens, together with strengthened bone health monitoring protocols, are advisable. Given the limited number of eligible studies and substantial heterogeneity, additional high-quality RCTs and individual patient data meta-analyses are needed to clarify these associations.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251102769.